Malaysia's ageing population : Viability of employment trust fund for retirement village - Lim, Chwee Tin (2010)
This study aims to analyse the Feasibility of Retirement Village for Malaysia.s Ageing Population. The analysis process involves assessing the level of awareness and opinion in the respondents of the demand for Retirement Village in Malaysia using survey method. At the macro level perspective, an overview analysis of the social, economic, political and technical knowhow of implementing and operating a Retirement Village has been taken into consideration to verify the advantages and disadvantages of the ultimate plan for Retirement Village. In order to satisfy the need for the public and acceptance of the idea to retire at Retirement Village, a detailed study and literature review of the practical reason for the implementation was intended to derive a mechanism for the suggested plan, to explore whether it to be workable in this country. Hence, a structured plan by private sector to establish a trust fund for Retirement Village as part of employee benefit was investigated to explore whether a potential demand and supply of the study is completely balanced. The motivation for the study was intended to build the first Retirement Village for the middle class elderly in Malaysia, therefore the senior citizens can enjoy a good lifestyle after retirement instead suffering from mental distress of living alone at their existing homes. The motivation is also partly due to the fact that the public general has a wrong perception that living in Retirement Village is the abandonment of parents by their loves ones which is completely wrong. The test itself would be able to confirm at the level information available to Malaysians and the knowledge they possessed about Retirement Village. There is much literature on Employee Loyalty, Motivation, Employee Benefits and Corporate Social Responsibility. However, there are no calls to extend the purpose of the literature study to apply in the companies in Malaysia to create economic and social value to the Malaysia Economic Productivity and Social Welfare improvement. This research is a comprehensive study because there is a recommendation to adapt Corporate Social Responsibility Core Value at Work Place to improve Employee Loyalty, increase Motivation and improve retention via the implementation of Employee Benefit to encourage the private sector to implement a Retirement Trust Fund for Retirement Village for their long-serving employees. As such, the retention of talents can be achieved due to better job security and loyalty. And, the employer can improve their productivity due to less time spent on retraining new employees and handling recruiting work from time to time. Due to the lack of availability of literature to assess the Feasibility of Retirement Trust Fund for Retirement Village in the context of Malaysia.s ageing population, this study can also motivate the researcher to explore further. The study herewith will be part of Greenfield study that requires further research in the future to confirm certain aspects of the findings. Further to that, this study is very relevant for Malaysia context because this is a pioneering research in the viability of Trust Fund for Retirement in Malaysia. Currently, there is no public or private owned Retirement Village being built in Malaysia which has motivate the researcher to take the challenge to assess the viability. The study involves relative demographic of the respondents in correlation to the knowledge and opinions of the Retirement Village. Generally, the study was carried out in Kuala Lumpur and Petaling Jaya, which is an Urban and Suburb respectively of Malaysia which comprises approximately 71 million populations. The respondents were mostly educated adults from different education backgrounds and various age groups to derive a good mix of sensible responses. Our result reveals that generally not all Malaysians are aware of the terminology of Retirement Village and not certain of the benefits living in the retirement village due to the lack of awareness and non-availability of the services in Malaysia. However, for those who are aware of the Retirement Village, they are basically receptive of the idea that it is a good place to adapt healthy, independent lifestyle retirement for senior citizen. From the overall result it reveals that the majority of the respondents from the ages of 31 to 40 look forward to retire in the Retirement Village and enjoy a community living lifestyle. This is despite the fact that these Malaysians are strong in Asian Extended Family Culture and they are also educated and married. The test also suggested that man are more independent in Malaysia and are very positive in Retirement Village lifestyle and single females surpassed married females in the preference to live in the Retirement Village. The research also concluded that three quarters (3/4) of the respondents have their opinions that their current Employee Provident Funds (EPF) is insufficient for their old age retirement, a total combined of 80.6% of the respondents have an opinion that private sectors should set up a trust fund for Retirement Village for their long serving employees, a combine total of 71% of the respondents have revealed that the Government should impose rules on private sectors to set up a trust fund for the Retirement Village for their long serving employees, an average combined 77% of the respondents have agreed that the Government should provide tax incentives to property developers to build Retirement Village and a combined average 71% of the respondents in their opinion that the Government should provide tax incentives to the tax payers for specific investment in the Retirement Village. Several implications arise from the study, firstly there is no supply in the building industry conglomerate that is willing to venture into this business unless it is certain that the monthly maintenance charges for the senior citizens are rest assured by their former employer or companies. Secondly, there is an issue of sustainability of the company to provide such a large scale employee benefit which is not feasible unless they adhere strictly to the CSR Core Values and there are more incentives cum tax subsidies from the policy maker to drive this purpose into reality. Thirdly, there is lack of expertise in the healthcare system in Malaysia that may require more time and money for training before the real implementation of the pilot project. Fourthly, the expectation from the Malaysian population now is already exists but there is no supply of the services. Lastly, the social economic changes, there are more going to have accelerated growth of singles, divorce group and single-child family in the population that require to live in the Retirement Village. This suggests critical reason that various preparation works such as training of expertise in healthcare services for senior citizens can be accelerated and increased.